Programa de intervenção com mães de adolescentes em conflito com a lei - Hauer Junior, Alfredo (2017)
Parental practices are strategies used by parents in guiding their children. When these strategies take place adequately and positively, the learning of pro-social behaviors is favored; when it is inappropriate, antisocial behaviors can be learned by bringing the child or adolescents closer to the offending behavior. One of the forms of prevention and treatment of antisocial and infractional behavior is training with responsible parents or caregivers. The objective of this research was to evaluate an intervention program with mothers of offending adolescents in a Socioeducation Center of a medium size municipality in the State of Paraná. The program was developed in 12 sessions, one hour and thirty minutes. The topics covered in the program were; affection, assertiveness, communication, politeness, positive and negative parenting practices, functional analysis, self-esteem, justice and forgiveness. Four mothers aged between 35 and 58 years old participated in this study, whose children fulfilled socio-educational measures in a closed regime due to homicide, robbery, drug trafficking and robbery. The program was evaluated through the Inventory of Parenting Styles - IEP and Self Assessment Inventory for adults aged 19 to 59 years - ASR, used in pre, post and follow up. The Family Injury History (HIF) was also used to characterize the sample. The HIP indicated the presence of offending behavior in partners, parents and grandparents. Positive parenting practices increased after intervention and negative practices decreased. In ASR there was improvement in scores in almost all variables, especially friends, externalizing problems, internalizing problems and withdrawal. This study points to the possibility of intervention with mothers of adolescents in conflict with the law with a significant increase of positive practices that are inhibitors of antisocial behavior.